Digital Strategies, Workforce Skills, and the Path to Financial Resilience - Retnosari; Wahyudi, Muhamad (Inovasi Analisis Data, 2025)
Purpose: The focus of this paper is on how digital transformation, digital strategy, technology investments, workforce digital skills and customer engagement can help to build financial resilience. The moderating role of environmental uncertainty in these relationships is also examined.Method: A quantitative survey method was employed, with structured questionnaires used to collect data from businesspeople. The data were analysed using advanced regression techniques. These techniques were used to assess direct as well as conditional effects. The firm level variables were also retained.Findings: The findings reveal that all aspects of digital transformation show a significant positive relationship with financial resilience, with workforce digital skills being the most influential dimension. Furthermore, environmental uncertainty amplifies the impact of digital capabilities, providing evidence that turbulent times may be more valuable in terms of an organisation's digital preparedness. These results lend support to the combination of dynamic capabilities and contingency views, as well as to an extension of the resource-based view that emphasises human capital.Novelty: The literature on resilience is extended by this study through the demonstration that an even more strategic form of competitive advantage than technology investments is offered by digital talent and skills. It also provides empirical support that uncertainty is not always a barrier to organisations, but rather can help maximise the benefits from digital transformation.Implications: The findings imply that organisations will need to invest in a broad-based digital strategy and workforce development, as well as restructuring organisational practices for learning and developing human capability. To this end, policymakers may need to develop interventions that encourage and nurture digital capabilities, whilst also promoting ecosystem collaboration to enhance long-term resilience.